The design and hardware-in-the-loop simulation test of a parallel hybrid transmission control system. (20th February 2004) - Marco, J.; Ball, R.; Jones, R.P.; Roxburgh, A.
Presented within this paper is the design and hardware-in-the-loop simulation test, HILST, of the transmission control system for the HERO vehicle. The acronym HERO refers to hybrid electric realised off-road, which constitutes a parallel hybrid derivative of a Land Rover Defender. The powertrain comprises of an electrical machine mechanically coupled to the gearbox input shaft. The transmission control system employs the electrical machine to actively assist in the gear change process. The simulated performance of the control system is compared to the results obtained when the control algorithms have been converted to a source code program and compiled to the control module operating within a HILST environment.